Turkish Archives of Pediatrics 2024
DOI: 10.5152/turkarchpediatr.2024.23126
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden and Depression in Parents of Children with Chronic Diseases

Şenay Güven Baysal,
Seniha Çorabay

Abstract: Objective: Caregiver burden is a factor that caregivers undertake for patients with chronic diseases and individuals in need of care. Depending on the symptoms of the disease and the processes following the diagnosis, depression problems may develop in caregivers. In this study, it was aimed at determining the caregiving burden of parents who have children with chronic diseases, the condition of special needs, and the factors that affect this burden. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In this study, coping and social support represent protective factors, whereas emotional stress and caregiver burden constitute risk factors. Chronic negative emotions can impede parental coping mechanisms ( Koutelekos et al, 2023 ), while social support has been shown to alleviate such emotions, whereas caregiver burden exacerbates them ( Guralnick et al, 2008 ; Güven Baysal and Çorabay, 2024 ). Moreover, the presence of social support can mitigate caregiver burden ( Adib-Hajbaghery and Ahmadi, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, coping and social support represent protective factors, whereas emotional stress and caregiver burden constitute risk factors. Chronic negative emotions can impede parental coping mechanisms ( Koutelekos et al, 2023 ), while social support has been shown to alleviate such emotions, whereas caregiver burden exacerbates them ( Guralnick et al, 2008 ; Güven Baysal and Çorabay, 2024 ). Moreover, the presence of social support can mitigate caregiver burden ( Adib-Hajbaghery and Ahmadi, 2019 ).…”
Section: Introductionmentioning
confidence: 99%